2022
DOI: 10.7759/cureus.24241
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Cryptogenic Stroke in a Patient With Left Atrial Septal Pouch

Abstract: The incomplete fusion of the septum primum and septum secundum results in the formation of the left atrial septal pouch (LASP). The clinical significance of this entity is a matter of controversy; however, it may act as a nidus for thrombus formation. We report a case of a 57-year-old male who was brought to the hospital by his girlfriend due to his bizarre behavior and confusion for one day. The initial workup for his altered mental status did not yield a diagnosis. The patient was admitted for further workup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A recent case report was presented with a case of recurrent thromboembolic conditions in a patient with normal sinus rhythm and no other cause of thrombus other than LASP [21]. One case-control study reported prevalence rates of LSP in stroke patients and control individuals (28.9% vs. 29.3%; p = 0.93).…”
Section: Association Between Lasp and Cryptogenic Strokementioning
confidence: 99%
“…A recent case report was presented with a case of recurrent thromboembolic conditions in a patient with normal sinus rhythm and no other cause of thrombus other than LASP [21]. One case-control study reported prevalence rates of LSP in stroke patients and control individuals (28.9% vs. 29.3%; p = 0.93).…”
Section: Association Between Lasp and Cryptogenic Strokementioning
confidence: 99%